The ethics of Aristotle - Koterski, Joseph W.; Teaching Company (Chantilly, VA : The Teaching Co., 2001)
Professor Joseph Koterski of Fordham University delivers lectures on Aristotle's views on morality.
The philosopher of common sense -- What is the purpose of life? -- What is moral excellence? -- Courage and moderation -- The social virtues -- Types of justice -- The intellectual virtues -- Struggling to do right -- Friendship and the right life -- What is friendship? -- Pleasure and the right life -- Attaining true happiness.
Keywords: Philosophy, Ancient